Molecular Analysis of B Lymphocyte Development and Activation - Singh, Harinder; Grosschedl, Rudolf; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
The B lymphocyte lineage represents an important paradigm for exploring the molecular mechanisms underlying cell fate specification, differentiation and cellular activation. In the past five years, major advances have been achieved in our understanding of the transcriptional control of early B cell development and terminal plasma cell differentiation. In addition new insights became available for the processes of B cell activation, class switch recombination and somatic hypermutation. Many of the new findings and their implications for a molecular understanding of B cell biology in particular and cell differentiation in general are covered in this volume.
Gene Regulatory Networks Orchestrating B Cell Fate Specification, Commitment, and Differentiation -- Helix-Loop-Helix Proteins in Lymphocyte Lineage Determination -- Ikaros-Family Proteins: In Search of Molecular Functions During Lymphocyte Development -- Biochemistry of V(D)J Recombination -- The pre-B cell Receptor in B Cell Development: Recent Advances, Persistent Questions and Conserved Mechanisms -- Transcriptional Control of B Cell Activation -- Expression of MHC II Genes -- Class Switch Recombination: An Emerging Mechanism -- Blimp-1; Immunoglobulin Secretion and the Switch to Plasma Cells -- Wnt Signaling in Lymphopoiesis.
Keywords: Immunology; Immunology